2020
DOI: 10.2174/1573407214666180808124802
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Evaluation of Novel Benzimidazole Fused Condensed Thienopyrimdines Derivatives

Abstract: Background: Cancer is a major health problem acting as a global killer and one of the leading causes of death. Most cancer chemotherapeutic drugs currently in clinical use are to kill malignant tumour cells by inhibiting some of the mechanisms implied in cellular division. Thienopyrimidines occupy a special position among the fused pyrimidines, along with other pyrimidines containing an annelated five membered hetero aromatic ring; forms a significant class of drugs which exhibit an array of various biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The 1 H ‐benzimidazole‐2‐one‐thieno[2,3‐ d ]pyrimidin‐4(3 H )‐one hybrid 49 (IC 50 : 29.0 and 74.0 nM, MTT assay) exhibited pronounced activity against MCF‐7 and MDA‐MB‐231 breast cancer cell lines, demonstrating its potential as a novel antibreast cancer candidate. [ 105,106 ]…”
Section: Benzimidazole‐pyrimidine Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H ‐benzimidazole‐2‐one‐thieno[2,3‐ d ]pyrimidin‐4(3 H )‐one hybrid 49 (IC 50 : 29.0 and 74.0 nM, MTT assay) exhibited pronounced activity against MCF‐7 and MDA‐MB‐231 breast cancer cell lines, demonstrating its potential as a novel antibreast cancer candidate. [ 105,106 ]…”
Section: Benzimidazole‐pyrimidine Hybridsmentioning
confidence: 99%
“…[104] The mechanistic study revealed that hybrid 48 and MDA-MB-231 breast cancer cell lines, demonstrating its potential as a novel antibreast cancer candidate. [105,106]…”
Section: Benzimidazole-cinnamic Acid Hybridsmentioning
confidence: 99%
“…In this comprehensive review, we focused on the role of benzimidazole in the treatment of cancer disease. Benzimidazole is a fusion of a six-membered benzene ring and a five-membered imidazole/imidazoline ring, which is an azapyrrole in the nucleus (Kaliraj & Kathiravan, 2020).…”
Section: Introductionmentioning
confidence: 99%